Carboidrases em programas enzimáticos de rações para frangos de corte - Sorbara, José Otávio Berti (2008)
Three experiments were performed in the experimental poultry house of Maringá State University to evaluate the performance of broilers, production cost and ileal apparent digestibility of feed supplemented with different carbohydrases enzyme programs at different ages. The first trial was carried out to evaluate the possibility of supplementing corn and soybean meal based diets for broilers after 21 days of age with exogenous enzymes. A complete randomized design was used with four treatments and five replicates with 34 birds each. The treatments included a positive control (PC); a negative control (NC) with a 120 kcal/kg reduction of the metabolizable energy (ME) in the PC; NC+amylase (AMI); and NC+AMI+ xylanase (XIL) from 21 to 40 d. The body weight gain (BWG) was reduced in the broilers fed the NC diet. However, when the birds were fed the NC diet + AMI+XIL, the BWG improved and reached the same level as the PC. The economic evaluation demonstrated that enzymes reduce cost production by 4 to 15% depending on the cost of feed ingredients and the enzymes that were used. A complete randomized design was also used in the second trial. Two treatments were used from 1 to 19 days of age, with 32 replicates each with 36 birds each: a PC (without enzyme) and a PC+AMI. Eight treatments were used from 20 a 40 days of age, with eight replicates. Each treatment of the starter phase was further divided into four during the grower phase. The four treatments of the grower phase originated from the starter phase that did not include enzymes were: PC, NC with 120 kcal less than PC, NC+AMI and NC+AMI+XIL. The other four treatments in the grower phase originated from the starter phase with amylase supplementation were: PC+AMI, PC+AMI+XIL, NC+AMI, NC+AMI+XIL. The treatment PC+AMI in the starter phase had higher (P<0.05) feed intake than the PC. The ME reduction by 120 kcal/kg in the growing phase had great impact on the feed conversion rate (FCR) which was higher for the NC group than for the PC. However, even though the performance parameters improved when enzymes were used, none of the enzyme supplementation programs was efficient enough to reach xii the PC parameters (P>0.05). The economic evaluation shows that all the enzyme supplementation programs resulted in a reduction of the cost production per kg of live body weight, based on the present prices of feedstuffs or higher. A complete randomized design was used in the third trial, with seven treatments and eight replicates in the starter phase, except for the PC treatment that had 16 replicates in this phase. The starter phase treatments were: PC, NC50, NC75 and NC100 with 50, 75 and 100 kcal less than PC, respectively, NC100+AMI, NC100+AMI+XIL and NC100+Glucanase (GLU). In the grower phase, 8 treatments with 8 replicates were used and the PC treatment was further divided into two treatments, one remaining as PC and the other receiving NC100+AMI. The other difference was that the group receiving the NC100+GLU treatment in the starter phase received NC100+AMI+XIL in the grower phase. At 19 and 40 d of age, 10 and 5 birds/replicate, respectively, were euthanized and the ileum contents collected to determine the ileal apparent digestibility of the feeds that were used in the treatments. It was found in this experiment that it was necessary to lower the ME by 100 kcal/kg in order to detect a worsening in FCR when comparing the PC with the NC. During the starter phase, none of the enzyme supplementation programs that were used was able to achieve the performance parameters obtained in the PC group. However, the group that received NC+AMI in the growing phase and the PC feed in the starter phase had better (P<0.05) FCR and BWG than NC100. The performance improvement obtained using NC+AMI only in the growing phase could not be explained by the ileal apparent digestibility data. The economic analysis demonstrates that enzyme supplementation depends on the enzyme program used and the price of feedstuffs. Based on the results obtained it can be stated that the use of enzymatic program with AMI or AMI+XIL supplementation only after 19 d of age has a positive effect on broiler performance.